Sharing knowledge for policy action in low- and middle-income countries: A literature review of managed entry agreements. Issue 1 (March 2019) - Castro, Hector E.; Malpica-Llanos, Tanya; Musila, Ruth; Konduri, Niranjan; Amaris, Ana; Sullivan, Jennifer; Gilmartin, Colin
Managed entry agreements (MEAs)—a type of formal institutional arrangement between pharmaceutical companies and payers for sharing the risk with respect to the introduction of new pharmaceutical technologies—may expand access to new pharmaceutical technologies for non-communicable diseases (NCDs). Although common in highincome countries (HICs), there is limited evidence of their use in low- and middle-income countries (LMICs). This article aims to document international experiences of countries implementing MEAs and potential barriers and facilitators for their use in LMICs. We reviewed published literature sources on MEAs over the past 10 years considering peer-reviewed publications and gray literature data. We took into consideration the MEAs taxonomy presented by Kanavos and Ferrario et al. to categorize our findings, and extract information on factors for their implementation. We retrieved 285 MEAs documented in the literature, mostly from HICs and for a broad spectrum of NCDs. Financial schemes were slightly more prominent than performance-based agreements. Identified factors that could potentially facilitate or hinder the implementation of MEAs included the presence of quality administrative and information systems to track their implementation; availability of quality data and evidence of positive outcomes; uncertainty of drug efficacy/effectiveness, safety, and financial impact; and cultural factors, namely country's preference for certain type of agreement and trust among payers and manufacturers. The increased availability of publications in recent years suggests a growing interest among policy-makers and researchers in the implementation of MEAs. While the use of MEAs in LMICs is very limited, this could be the result of limited empirical evidence on its use and possibly due to the use of a different taxonomy for describing MEAs in these settings. As any other policy option, the implementation and use of MEAs come with advantages and challenges. Since there is limited evidence on their use in LMICs, the identified cases of implementation in HICs may serve to inform the interest on MEAs in resource limited settings. Therefore, further research in this field especially in the context of LMICs may be of value for the global community as all countries are embarking into fairer and sustainable Universal Health Coverage (UHC).